Métodos diagnósticos y terapéuticos de la tenosinovitis de quervain - Samaniego Vivanco, Daniela Cristina (Machala : Universidad Técnica de Machala, 2023)
Quervain's tenosynovitis, also called Quervain's stenosing tenosynovitis, named after the Swiss surgeon Fritz De Quervain, who first described it in 1895. This disease affects the extensor pollicis brevis tendons of the thumb and abductor pollicis longus, is a common condition of the wrist, which occurs with a prevalence of 0.5% in men and 1.3% in women with a higher frequency of presentation in the range of 40 and 50 years of age. Objective: To describe the different types of diagnostic and therapeutic methods of Quervain's tenosynovitis through a review of the literature in order to update the existing information for the benefit of health professionals. Methodology: A descriptive, retrospective study was carried out through the review of 15 bibliographies obtained from databases such as Pubmed, Scielo, Cochrane and academic Google of the last 5 years, in addition to the use of the Scimago tool for checking the quartile of the articles used. Conclusion: The diagnosis of Quervain's tenosynovitis is made through clinical and physical examination by means of several tests such as Finkelstein, Eichhoff, WHAT, and ultrasound is also useful. Among the most widely used therapies are conservative methods such as local ice, massage, physical therapy, another method is non-surgical which includes kerosene baths, injection of corticosteroids blindly or guided by ultrasound and thumb splinting and in recurrent cases surgical treatment is used.
La tenosinovitis de Quervain, también llamada tenosinovitis estenosante de Quervain, denominada de esta manera en honor al cirujano suizo Fritz De Quervain, quién la describió inicialmente en 1895. Esta enfermedad afecta a los tendones extensor corto del pulgar y el abductor largo del pulgar, es una condición común de la muñeca, la cual se presenta con una prevalencia del 0.5 % en hombres y del 1.3% en mujeres con mayor frecuencia de presentación en el rango de 40 y 50 años de edad. Objetivo: Describir los distintitos tipos de métodos diagnósticos y terapéuticos de la Tenosinovitis de Quervain a través de revisión de bibliografía para actualizar la información existente en beneficio de los profesionales de la salud. Metodología: Se realizó un estudio descriptivo, retrospectivo a través de la revisión de 15 bibliografías obtenidas de las bases de datos como Pubmed, Scielo, Cochrane y Google académico de los 5 últimos años, además del uso de la herramienta Scimago para la comprobación del cuartil de los artículos empleados. Conclusión: El diagnóstico de la tenosinovitis de Quervain se lo realiza a través de la clínica y la exploración física mediante varios test como el de Finkelstein, Eichhoff, WHAT, además de la ecografía. Entre las terapias más usadas se encuentran los métodos conservadores como el hielo local, masajes, terapia física, el método no quirúrgico que incluye baños de parafina, inyección de corticoesteroides a ciegas o guiada por ecografía y la férula del pulgar y en casos recidivantes se recurre el tratamiento quirúrgico.
Keywords: TENOSINOVITIS DE QUERVAIN; TENDINITIS; TENDONES; COMPARTIMENTO